Alarming Floods in Indian Cities: Strengthening Institutional Capacities for Management - Ronak Mehta, Hriday (Iapa Proceedings Conference, 2024)
Floods are among the most dangerous natural disasters, statistically impacting more lives and properties than any other calamity. According to the National Disaster Management Authority (NDMA), India witnessed over 400 major floods between 1953 and 2018, affecting approximately 56 million people and causing damages amounting to $100 billion. This paper discusses methods institutions in India could adopt to mitigate the effects of floods. The research methodology includes primary research through personal interactions with bureaucrats and technocrats in the field of management, as well as with staff from the National Disaster Response Force (NDRF). Additionally, secondary research comprises qualitative analyses of data, reports, and various journal papers. Findings emphasize the necessity of participative governance and inter-departmental coordination to minimize damage. Recommendations include preventive measures through infrastructure development and staff training, thorough prior licensing of industries, collaboration with meteorological departments and NGOs, standardization of rescue team procedures, and active engagement from policymakers. The roles of efficient committees and public participation are underscored, alongside the need for collaboration among technical and managerial departments—such as water, irrigation, rapid action, and medium-range weather forecasting. The paper offers a scientific approach to tackling floods and serves as a reference for policymakers, bureaucrats, and committees focused on flood prevention and management.